O sentido de aprender matemática acerca da fórmula de Bhaskara - Santos, José Aldon Garção (2011)
Regarding the experiences of the ninth graders students from primary school, when they study both quadratic equation and Bhaskara s formula, this research examines what the sense of the Mathematics learning for public schools students from Itabaiana/SE. This is a both qualitative research, and it intends verifying how a student mobilized himself to learn those math subjects, focusing on the quadratic equation and Bhaskara s formula, it seeks understanding the relation with the knowledge at this stage of learning. The theoretical contribution comes from the theories of Bernard Charlot (2007, 2005), Silva (2009), Boyer (2004) among others. The data collected through observation of classes, with the use of questionnaires and interviews reveal that the mathematics learning, specifically the quadratic equation and Bhaskara s formula, is directly influenced by the presence of the didactical textbook which, along with the teaching practices, has contributed to this content to be viewed as irrelevant to the student future, giving the prevail to the momentary memory (learn by heart) and not to the effective learning.